Campaña de lanzamiento de la nueva bebida energizante Boom Power en Lima Metropolitana - Montenegro Calenzani, Maria Jose (2023)
According to Euromonitor's Energy Drinks in Peru report, in 2022 there was an increase in energy drink sales, as consumers returned to their old lifestyles that were paused by the COVID 19 pandemic. For this reason, the company Bebidas Nacionales S.A.C. plans to launch its new energy drink ¨Boom Power¨, made of taurine, guarana, ginseng, maca, caffeine, theine and sweetened with yacon. In order to present a plan, we have carried out market research and its main competitors. We will present the product launch campaign, which covers the communication strategy both on and offline focused on the consumer. Beyond being able to achieve a 12% market share at the end of the first year of operations, we want to make the brand known among young people from Lima between the ages of 18 and 30, of socioeconomic level C, who lead an active life and experience daily situations that require a boost of energy. Our differential is based on the fact that this drink will reinforce the performance of the daily activities of young Peruvians and will highlight the natural ingredients from the central highlands, thus making Boom Power a national energy drink.